1994
DOI: 10.1056/nejm199401203300301
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial Comparing Preoperative Chemotherapy Plus Surgery with Surgery Alone in Patients with Non-Small-Cell Lung Cancer

Abstract: Preoperative chemotherapy increases the median survival in patients with non-small-cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
438
0
25

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,170 publications
(484 citation statements)
references
References 27 publications
7
438
0
25
Order By: Relevance
“…On the other hand, several phase III studies have shown that cisplatincontaining induction chemotherapy may increase survival rate in stage IIIA or IIIB locally advanced non-small cell lung cancer (LAD-NSCLC) patients. Two randomized studies demonstrated increased survival in stage IIIA NSCLC patients if two to three cycles of chemotherapy were given before surgery (Rosell et al, 1994;Roth et al, 1994). In inoperable patients, induction with cisplatin plus vinblastine followed by radiotherapy demonstrated long-term survival advantage over radiotherapy alone in a randomized study (Dillman et al, 1996) and was confirmed subsequently by an intergroup study (Sause et al, 1995).…”
mentioning
confidence: 93%
“…On the other hand, several phase III studies have shown that cisplatincontaining induction chemotherapy may increase survival rate in stage IIIA or IIIB locally advanced non-small cell lung cancer (LAD-NSCLC) patients. Two randomized studies demonstrated increased survival in stage IIIA NSCLC patients if two to three cycles of chemotherapy were given before surgery (Rosell et al, 1994;Roth et al, 1994). In inoperable patients, induction with cisplatin plus vinblastine followed by radiotherapy demonstrated long-term survival advantage over radiotherapy alone in a randomized study (Dillman et al, 1996) and was confirmed subsequently by an intergroup study (Sause et al, 1995).…”
mentioning
confidence: 93%
“…[4][5][6][7][8] Two of these studies involved small cohorts (n ¼ 60) that included mainly stage IIIA, N2 disease, and showed a significant survival advantage associated with induction chemotherapy compared with surgery alone. 5,6 None of the other trials reported any beneficial outcome for bimodality therapy compared with surgery alone.…”
mentioning
confidence: 99%
“…Several small randomised studies (Pass et al, 1992;Rosell et al, 1994;Roth et al, 1994) have demonstrated a benefit from neoadjuvant treatment in locally advanced disease (stage IIIA). In a large trial involving 355 patients with stage IB -IIIA NSCLC, a trend towards survival benefit was seen from neoadjuvant chemotherapy (median survival 37 months vs 26 months for surgery alone; P ¼ 0.15) (Depierre et al, 2002).…”
mentioning
confidence: 99%